Treatment of pediatric anxiety disorders. (November 2013) - Rapp, Amy; Dodds, Alice; Walkup, John T.; Rynn, Moira
Abstract : This article provides a brief review of the current available data concerning present treatment and potential new treatment advances for pediatric anxiety disorders, such as generalized anxiety disorder, separation anxiety disorder, social phobia, obsessive–compulsive disorder, and posttraumatic stress disorder. Disorder‐specific treatment methods and innovations, particularly computer‐assisted methods of delivery for cognitive behavioral therapy (CBT) will be reviewed. Additionally, the paper will discuss novel psychopharmacological compounds (e.g., d ‐cycloserine, riluzole, memantine, and anticonvulsant medications). Available evidence for the efficacy of novel medication strategies in adult studies and implications for their use in pediatrics will be discussed.